PENGARUH KREDIT CEPATAMAN TERHADAP PROFITABILITAS PADA PT. PEGADAIAN (PERSERO) UPC PASAR BAWAH BANGKO (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose ofthis researchis tofind outthe magnitude oftheEffect of Safe Fast Credit on Profitability at PT. Procurement (Persero) Bangko lower market UPC. This research is important because fast secure loans have a large contribution in the company's profitability of 82.4%.This research is a type of descriptive research. The study population is the financial statement data concerning the creditor and company profits of PT. Bangko lower market UPC for 5 (five) years, namely (2014 - 2018) and the analytical tool used is simple linear regression.The results of the research conducted showed that the effect of safe credit has a positive and significant effect on the profitability of PT. Procurement (Persero) Bangko lower market UPC.